Hubungan antara Problematic Internet Use dengan Prokrastinasi Akademik pada Mahasiswa Universitas Negeri Malang - Ilviana Yulia Sari; Freya Odelia Affandi; Nur Rohmah Hidayatul Qoyyimah; Femmi Nurmalitasari (Flourishing Journal, 2022)
The development of technology at this time makes everyone easily access the internet, especially college students. College students can easily access the internet to help in finding references for assignments in their lectures. However, the internet also has a negative impact if the internet is used inappropriately. The negative impact of the internet is problematic internet use. This study aims to determine the relationship between problematic internet use and academic procrastination in Malang State University college students. The instruments used in this study were the Generalized Problematic Internet Use Scale-2 (GPIUS-2) scale by Caplan (2010) and the Academic Procrastination Scale (APS) scale by McCloskey (2011). The data analysis used in this study consisted of categorisation tests and correlation tests using statistical calculations through the help of the Statistical Package for Social Science (SPSS) for Windows version 22 computer program. The results showed that there was a positive relationship between the problematic internet use variable and the academic procrastination variable in active internet user college students at State University of Malang Abstrak Perkembangan teknologi membawa dampak terhadap kemudahan mengakses internet, terutama pada mahasiswa. Mahasiswa dapat dengan mudah mengakses internet untuk membantu dalam mencari referensi untuk tugas dalam perkuliahannya. Namun, internet juga memberikan dampak negatif apabila penggunaan internet dilakukan secara tidak tepat. Dampak negatif dari internet tersebut dinamakan problematic internet use. Tujuan dari penelitian ini adalah untuk mengetahui interaksi antara problematic internet use dengan prokrastinasi akademik pada mahasiswa Universitas Negeri Malang. Instrumen yang digunakan pada penelitian ini adalah skala Generalized Problematic Internet Use Scale-2 (GPIUS-2) oleh Caplan (2010) dan skala Academic Procrastination Scale (APS) oleh McCloskey (2011). Analisis data yang digunakan dalam penelitian ini terdiri dari uji kategorisasi dan uji korelasi menggunakan perhitungan statistik dengan program komputer SPSS for Windows versi 22. Hasil penelitian menunjukkan adanya hubungan yang positif antara variabel problematic internet use dengan variabel prokrastinasi akademik pada mahasiswa di Universitas Negeri Malang